Wybrane aspekty duchowości biblijnej w pismach św. Urszuli Ledóchowskiej - Pagacz, Małgorzata (Poznańskie Studia Teologiczne, 2021)
The aim of this article is to present selected aspects of the biblical spirituality according to writings of Saint Ursula Ledóchowska. The Word of God has the central position in the spirituality of the Founder of the Congregation of the Ursuline Sisters of the Agonizing Heart of Jesus. Mother Ledóchowska is the author of Meditations, that contain considerations based on specific fragments of the Gospel, intended for each day of the year. Her Testament is also full of biblical references and permeated with the evangelical logic. According to Saint Ursula Ledóchowska the meditation of the Word of God in the spirit of faith enables us to learn more and get to know better the person of Jesus Christ and to deepen the relationship with Him. Mother Ledóchowska, by her attitude to the Holy Bible, was ahead of the Second Vatican Council’s time. All her life was an active exegesis of the words of Christ.